The Relationship Between Complementary Feeding and Stunting Eventsin 2 to 5 Years of Age - Sefrina Rukmawati; Puji Astutik; Puji Rahayu Slamet (Journal for Quality in Public Health, 2020)
Background : Lack of complementary feeding for children, from the age of 6 months complementary feeding begins to be necessary. Food that not good enough in both quality and quantity would affect stunted growth. Purpose : This research was to determine the relationship of complementary feeding with the stunting in 2 to 5 years of age Method : of this research is a retrospective approach. This research is carrying on March 4 2020. The population of this research is one of the parents and children aged 2-5 years as many as 22 people. Sampling retrieval using total sampling, totaling 22 parents and children. The independent variable of complementary feeding data collection with the questionnaire and the dependent variable stunting event data collection by the child's height measurement. Data analysis using spearman rank with α = 0.05. Results show that out of 22 respondents, nearly half of which were 10 respondents (45.5%) provide less complementary feeding in the category of less and children aged 2-5 years the majority of 16 respondents (72.7%) having heights in the short category. Correlation test results show p-value = 0.002 α = 0.05, so Ha is accepted. Conclusion : There is a relationship between complementary feeding with stunting in children aged 2-5 years, and r = 0.627 so the level of closeness is strong. In this research the becomes a strong predictor in caused the stunting, but was expected to further research can add various other variables to the stunting event.